Morphological and Genetic Variation in Mexican Wild Populations ofTamarixia radiata(Hymenoptera: Eulophidae) - Peña Carrillo, Kenzy Ivveth; González Hernández, Alejandro; López Arroyo, J. Isabel; Mercado Hernández, Roberto; Favela Lara, Susana (2015)
Recent developments of smart actuators using the two-way shape memory effect (TWSME) for industrial applications are becoming more common in scientific research. Shape memory alloys (SMAs) present some characteristics, which make it unique material to be use in applications that require strength and shape recovery. Ti-Ni alloys are an important class of memory alloys due to the shape memory effect (SME) and superelasticity (SE), which are govern by the thermoelastic martensitic transformation (MT). This material was been used to manufacture smart actuators for mechanical industry devices and several other applications in areas as medicine, robotics, aerospace, petroleum and gas industries. In general, Ti-Ni SMAs undergo one-step (austenite  martensite) transformation, but in some cases, there exists intermediate R-phase giving rise two-step (austenite  R-phase  martensite) transformation. This investigation is interesting due to the importance of knowing the actuators response to external stimulus (heat source, electrical current and/or external stress). In this work it was investigated the mechanical behavior in helical actuators produced from Ti-Ni alloy commercial wires. Different characterization techniques were employ for analyzing the samples as: differential scanning calorimeter (DSC), scanning electron microscopy (SEM), optical microscopy (OM) and a non-commercial apparatus developed to apply an external traction stress in helical actuators during thermal cycles.